Escaping social-ecological traps through tribal stewardship on national forest lands in the Pacific Northwest, United States of America - Long, Jonathan W.; Lake, Frank K. (Ecology and society, 2018)
Tribal communities in the Pacific Northwest of the United States of America (USA) have long-standing relationships to ancestral lands now managed by federal land management agencies. In recent decades, federal and state governments have increasingly recognized tribal rights to resources on public lands and to participate in their management. In support of a new planning initiative to promote sustainable land management, we reviewed scientific publications to examine relationships between tribal social-ecological systems and public lands in the region. We identified key ecocultural resources, impacts to those resources, and associated forest ecosystems, and strategies that have been piloted to redress those impacts. We found that many factors stemming from colonization by Euro-Americans have engendered social-ecological traps that have inhibited tribes from continuing traditional land stewardship activities that supported their well-being and maintained ecological integrity. These long-standing factors include legal and political constraints on tribal access and management; declining quality and abundance of forest resources due to inhibition of both natural disturbance and indigenous tending regimes; competition with nontribal users; species extirpations and introductions of invasive species; and erosion of tribal traditional ecological knowledge and relationships that are important for revitalizing resource use. As a consequence, both supply and demand for these forest resources have been reduced, as have the resilience and diversity of these ecosystems. Simply permitting resource harvest by tribal members does not sufficiently address the underlying constraints in ways that will promote tribal well-being. Escaping these traps will require addressing a gamut of ecological and social constraints through cooperative restoration efforts between land management agencies and tribes, several of which we highlight as examples. Because tribally focused restoration strategies generally align with broader strategies suggested to restore national forests in the region, they can foster both tribal well-being and ecological sustainability.